PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA SEKRETARIAT DAERAH KABUPATEN TEMANGGUNG) - Sri Hariyani, 11.52.02.0006 (Students Journal of Economic and Management, 2013)
This research aimed to analyze the effect of Work Environment and Motivation for Employee Performance with Organizational Commitment mediation. In this research population of 103 and taken all the number 108 as respondents quesioner method. Test instruments use validity and reliability, while the model test use R2 test (coefficient of determination), F test (Goodness of Fit) and t-test (t-test). Hypothesis Testing in this research use the regression analysis with t count criteria. Hypothesis testing is used t count frequency distribution test at significance level (Î±) of 5%. The results showed (1) Working environments have a positive and significant impact on Organizational Commitment, (2) Motivation has positive and significant impact on Organizational Commitment, (3) Working environments have a positive and significant impact on Employee Performance, (4) Motivation has positive and significant impact on employee performance, while (5) Organizational commitment does not mediate the effect of the Work Environment on Employee Performance and Motivation. Â  Keywords: Work Environment, Motivation, Organizational Commitment, Employee Performance